Pyreneacyl sulfides as a visible light-induced versatile ligation platform. Issue 32 (6th April 2017) - Tuten, Bryan T.; Menzel, Jan P.; Pahnke, Kai; Blinco, James P.; Barner-Kowollik, Christopher
Abstract : We report a visible light responsive moiety capable of generating highly reactive thioaldehydes. Abstract : We report a visible light responsive moiety capable of generating highly reactive thioaldehydes. Upon irradiation with visible light (420 nm) the pyreneacyl sulfide species undergoes a Norrish II elimination yielding thioaldehydes capable of being trapped by nucleophiles (amines, aminoxys, and thiols), as well as Diels–Alder processes, representing a new versatile ligation platform.